FLORISTIC SIMILARITY IN A FOREST-SAVANNAH ECOTONE IN WESTERN BAHIA STATE, BRAZIL - Treml, Leonardo De Marino; Cattarin, Anadia; Marques, Renato; Galvão, Franklin; Crivellari, Lucas Batista; Coutinho, Vinicius Morais (Floresta, 2022)
This study aimed to generate knowledge about transition areas between phytophysiognomies for the understanding and conservation of these unique environments. Thus, the existence of different floristic groups was analyzed in a spatial gradient of an ecotone in the municipality of São Desidério, state of Bahia, Brazil. To this end, a transect of approximately 4.7 km, with orientation from Northeast to Southwest, was established along a spatial gradient. Twelve (12) 10x50 m sampling plots (500 m² each) were distributed throughout this transect. The following methodology was employed: First, the floristic similarity between the sampling plots was measured. These sampling plots were then grouped and the data were graphically presented in a dendrogram (Cluster analysis) and an ordering diagram (nMDS). Finally, the phytosociological parameters by ordered group were obtained. The results showed the presence of three floristic groups: Groups I, II and III, classified as wooded savannah, seasonal deciduous forest, and forested savannah, respectively. The floristic groups were formed gradually along the spatial gradient, and transition between phytophysiognomies does not occur abruptly, since the ordering by groups is more due to the difference between the abundance of species than to their presence and/or absence. The distribution pattern of the phytophysiognomies along the spatial gradient indicates association with abiotic factors, such as the pedological characteristics and the relief found along the transect, possibly creating an environmental gradient.